Fracture analysis and low-temperature thermochronology of faulted Jurassic igneous rocks in the Southern Colombian Andes (2024)
Fractured basement hydrocarbon reservoirs are widely distributed worldwide in more than 30 basins, where volcanic and plutonic rocks have produced significant quantities of oil and gas. The Upper Magdalena Valley Basin (UMVB) is a mature and productive hydrocarbon basin located in the Colombian Andes. In this basin, plutonic and volcaniclastic Jurassic rocks are thrusted on top of Cretaceous to Cenozoic sedimentary rocks, which constitute the petroleum system. Multi-scale fracture analysis together with petrography, petrophysics, and low-temperature thermochronology were conducted in and outcrop analogue of this basement to assess the structural evolution and investigate the main factors controlling the development of fracture properties in igneous basements. Thermochronological data indicate the occurrence of three exhumation events between the Early Cretaceous and Miocene, suggesting that most of the fracture networks within the Agrado-Betania hanging-wall were likely formed before hydrocarbon migration. Structural analysis has identified a fault damage zone with a width of approximately 746 m. Volcanic breccias and ash tuffs exhibit slightly higher areal fracture intensities (P21 > 30 m/m2) compared to plutonic and clastic rocks (P21 < 20 m/m2). Furthermore, the fracture networks exhibit good connectivity, with connection per branch (CB) values exceeding the 1.5 percolation threshold. Petrophysical calculations of matrix-fracture properties indicate high permeabilities (ranging from 1000mD to 10000000mD) and low porosities (<10%). The structural position and the diagenetic transformation of the volcanic rocks are the primary factors controlling fracture intensity in the igneous rocks within the Agrado-Betania fault. Results from this outcrop analogue also show that polyphasic structural histories and the burial history positively influence the quality of fractured basement reservoirs.